Financial Inclusion of Small and Medium-Sized Enterprises in the Middle East and Central Asia - Blancher, Nicolas (Departmental Papers; Departmental Paper ;, 2019)
The importance of financial inclusion is increasingly recognized by policymakers around the world. Small and medium-sized enterprise (SME) financial inclusion, in particular, is at the core of the economic diversification and growth challenges many countries are facing. In the Middle East and Central Asia (MENAP and CCA) regions, SMEs represent an important share of firms, but the regions lag most others in terms of SME access to financing.